Distribution and Conservation Challenges of Diurnal Large Mammals in Bayo Community Managed Forest, Salamago Woreda, South Omo Zone, Southern Ethiopia - Tamirat Haile; Takele Serekebirhan (Journal of Zoological Research, 2023)
An ecological study on diurnal mammals was carried out in Bayo Community Managed Forest located in Salamago Woreda, South Omo Zone. The objective of the study was to investigate the distribution and conservation challenges of diurnal large mammals in the study area. Based on the habitat type and topography of the study area, total of 11 transect, i.e 7 in forestland, and 4 in Wooded Grassland were laid to collect the data. Besides direct methods, indirect methods such as faecal droppings, fresh tracks, carcass or shell count, den (burrow), hair, and digging were used. Questionnaire and focus group discussions were also used to assess anthropogenic threats in the study area. Data were analyzed using descriptive statistics, SPSS and QGIS software. A total of 20 species of diurnal large mammals belonging to six orders and eight families were identified. The species identified were Cercopithecus pygerythrus, Cercopithecus aethiops, Papio anubis, Erytherocebus patas, Cercopitheus neglectus, Colobus guereza, Equus quagga, Traglaphus strepsiceros, Traglaphus imberbis, Traglaphus scriptus, Medagua guentheri, Sylvicapra grimma, Kobus ellipsiprymnus defessa, Syncerrus caffer, Potamochoerus larvatus, Phacochoerus africanus, Hylochoerus meinertzhageni, Hystrix cristata, Orycteropus afer, and Phataginus temminckii smutus. Seasonal variation in the between habitat types (χ2 = 4.849, df= 1, p<0.05). Totally, 685 and 600 mammals were counted during wet and dry seasons, respectively. On habitat basis, 683 and 602 animals were recorded in forestland and wooded grassland habitats, respectively. Major threats in the study area include poaching, fire, grazing, fuelwood extraction, population growth, habitat modification, overharvesting of resources and invasive species. About 98.44% of respondents had a positive attitude towards Bayo Community Managed Forest. The interference of local community has had the impact on mammal’s species. Habitat based mammals’ management involving participation of Woreda and Zonal Government is recommended for sustainable. The local government should promote the study area and provide appropriate support for its conservation.
Keywords: Attitude